Teaching-learning in a Rehabilitation Teaching and Assistance Unit: Conceptions of Occupational Therapy students (Research, Society and Development, 2022)
This article aims to understand the students' conceptions of the professional internship in rehabilitation about learning lived in a laboratory of daily living activities in the context of a Teaching and Assistance Unit. This is a qualitative and exploratory study. A semi-structured interview was used for data collection and for interpretation, the content analysis technique proposed by Bardin with the thematic category learning. The sample consisted of 14 students from the 4th year of the undergraduate course in Occupational Therapy at the Universidade do Estado do Pará. The similarities and distinctions between the contents were observed, as well as the central ideas of the narratives were identified. The results obtained showed aspects not experienced by the students in the practice scenario, which interfered with learning, such as the absence of discussion of clinical cases, team meetings, socialization of situations that foster clinical reasoning for decision making. The students suggested reformulating actions to enable a more innovative and constructive experience in the practice environment.